UTILIZATION AND EFFECTIVENESS OF ARTIFICIAL INTELLIGENCE CHATBOTS IN MUNICIPAL LEGISLATIVE PROCESSES IN PANGASINAN, PHILIPPINES - V. Ahmed, Zshyna Mae; M. Victorio, Sylvester (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to assess the level of utilization and perceived effectiveness of Artificial Intelligence (AI) chatbots in enhancing the legislative functions of Sangguniang Bayan (SB) Members in the 2nd Congressional District of Pangasinan, Philippines, and to examine their relationship with the legislators' profile variables. Method: Using a descriptive survey method, data were collected to evaluate familiarity, usage patterns, and challenges associated with AI chatbot integration among local legislators. Results: Findings reveal that while most SB Members are aware of free AI chatbot models and use them for work-related functions such as research, engagement, and continuing education, overall utilization remains minimal. The tools are viewed as only moderately effective in supporting legislative processes. Key challenges include concerns over privacy and security, insufficient knowledge and skills, and legal and ethical considerations. Novelty: This study provides empirical insights into the cautious adoption of AI chatbots in local legislative contexts and underscores the critical need for comprehensive training programs to facilitate informed decision-making and promote innovative governance at the grassroots level.